Answer:
20x^2-10x+8
Step-by-step explanation:
8+x2-4x3 +5x 2x2
20x^2-10x+8
i hope this helps!
Answer:
C. r = d/2
Step-by-step explanation:
The radius is half of the diameter.
The diameter divided by 2 would equal the radius of a circle.
Answer:
she has 2/4 of the jug left. hope this helped a bit!
Step-by-step explanation:
3/4 - 1/4 = 2/4 or 1/2 (simplified)
The solution is ![x = 2 \text{ and } y = \frac{1}{2}](https://tex.z-dn.net/?f=x%20%3D%202%20%5Ctext%7B%20and%20%7D%20y%20%3D%20%5Cfrac%7B1%7D%7B2%7D)
<em><u>Solution:</u></em>
Let us assume,
![a = \frac{1}{x}\\\\b = \frac{1}{y}](https://tex.z-dn.net/?f=a%20%3D%20%5Cfrac%7B1%7D%7Bx%7D%5C%5C%5C%5Cb%20%3D%20%5Cfrac%7B1%7D%7By%7D)
<em><u>Given system of equations are:</u></em>
![\frac{2}{x} - \frac{3}{y} = -5](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7Bx%7D%20-%20%5Cfrac%7B3%7D%7By%7D%20%3D%20-5)
![\frac{4}{x} + \frac{6}{y} = 14](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7Bx%7D%20%2B%20%5Cfrac%7B6%7D%7By%7D%20%3D%2014)
<em><u>Rewrite the equation using "a" and "b"</u></em>
2a - 3b = -5 ------------ eqn 1
4a + 6b = 14 -------------- eqn 2
<em><u>Let us solve eqn 1 and eqn 2</u></em>
<em><u>Multiply eqn 1 by 2</u></em>
2(2a - 3b = -5)
4a - 6b = -10 ------------- eqn 3
<em><u>Add eqn 2 and eqn 3</u></em>
4a + 6b = 14
4a - 6b = -10
( - ) --------------------
8a = 4
![a = \frac{4}{8}\\\\a = \frac{1}{2}](https://tex.z-dn.net/?f=a%20%3D%20%5Cfrac%7B4%7D%7B8%7D%5C%5C%5C%5Ca%20%3D%20%5Cfrac%7B1%7D%7B2%7D)
Substitute a = 1/2 in eqn 1
![2(\frac{1}{2}) -3b = -5\\\\1 - 3b = -5\\\\3b = 6\\\\b = 2](https://tex.z-dn.net/?f=2%28%5Cfrac%7B1%7D%7B2%7D%29%20-3b%20%3D%20-5%5C%5C%5C%5C1%20-%203b%20%3D%20-5%5C%5C%5C%5C3b%20%3D%206%5C%5C%5C%5Cb%20%3D%202)
Now let us go back to our assumed values
Substitute a = 1/2 in assumed values
![a = \frac{1}{x}\\\\\frac{1}{2} = \frac{1}{x}\\\\x = 2](https://tex.z-dn.net/?f=a%20%3D%20%5Cfrac%7B1%7D%7Bx%7D%5C%5C%5C%5C%5Cfrac%7B1%7D%7B2%7D%20%3D%20%5Cfrac%7B1%7D%7Bx%7D%5C%5C%5C%5Cx%20%3D%202)
Substitute b = 2 in assumed value
![b = \frac{1}{y}\\\\2 = \frac{1}{y}\\\\y = \frac{1}{2}](https://tex.z-dn.net/?f=b%20%3D%20%5Cfrac%7B1%7D%7By%7D%5C%5C%5C%5C2%20%3D%20%5Cfrac%7B1%7D%7By%7D%5C%5C%5C%5Cy%20%3D%20%5Cfrac%7B1%7D%7B2%7D)
Thus the solution is ![x = 2 \text{ and } y = \frac{1}{2}](https://tex.z-dn.net/?f=x%20%3D%202%20%5Ctext%7B%20and%20%7D%20y%20%3D%20%5Cfrac%7B1%7D%7B2%7D)